2010
DOI: 10.1182/blood-2009-12-257212
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of CLEC-2 is dependent on lipid rafts, actin polymerization, secondary mediators, and Rac

Abstract: The C-type lectin-like receptor 2 (CLEC-2) activates platelets through Src and Syk tyrosine kinases via a single cytoplasmic YxxL motif known as a hem immunoreceptor tyrosine-based activation motif (hemI-TAM). Here, we demonstrate using sucrose gradient ultracentrifugation and methyl-␤-cyclodextrin treatment that CLEC-2 translocates to lipid rafts upon ligand engagement and that translocation is essential for hemITAM phosphorylation and signal initiation. HemITAM phosphorylation, but not translocation, is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 40 publications
11
106
0
Order By: Relevance
“…Previous studies have shown that Rac1 is activated in platelets by a number of agonists (45)(46)(47) and plays an important role in aggregation, secretion, and clot retraction. Interestingly, Rac1 is known to be essential for the regulation of PLC␥2 in platelets downstream of GPVI or CLEC-2 (48,49). In the presence of pharmacological inhibitors of Rac, as well as in Rac1-deficient murine platelets, agonistinduced dense granule secretion is inhibited (50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Rac1 is activated in platelets by a number of agonists (45)(46)(47) and plays an important role in aggregation, secretion, and clot retraction. Interestingly, Rac1 is known to be essential for the regulation of PLC␥2 in platelets downstream of GPVI or CLEC-2 (48,49). In the presence of pharmacological inhibitors of Rac, as well as in Rac1-deficient murine platelets, agonistinduced dense granule secretion is inhibited (50).…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of CLEC-2 evokes a similar set of signaling events as seen with GPVI, including tyrosine phosphorylation by SFK, Syk, and Tec-family kinases and signal complex assembly around scaffold proteins (313). Platelet stimulation via CLEC-2 relies on autocrine effects via release of secondary mediators like ADP and thromboxane A 2 (233). There is still discussion on the possible existence of a physiological ligand for CLEC-2 receptors on platelets, which could potentially be CLEC-2 itself (281).…”
Section: A Platelet Leucine-rich Repeat and Immunoglobulin Family Rementioning
confidence: 95%
“…However, a later study showed that neither CLEC-2 phosphorylation nor subsequent Syk activation depends on lipid raft integrity, leading to the proposal that lipid raft disruption inhibits the actions of secondary mediators necessary for CLEC-2-triggered platelet aggregation rather than directly interfering with CLEC-2 phosphorylation (85). In addition, CLEC-2 phosphorylation and activation of Syk were also inhibited when actin polymerization was blocked by cytochalasin D, whereas Syk activation stimulated by the ITAM-coupled GPVI receptor was unaffected (84). It remains to be shown whether membrane localization and actin polymerization also affect the function of other hemITAM receptors.…”
Section: Key Features Of Hemitam Signaling As Defined By the Prototypmentioning
confidence: 96%
“…CLEC-2 tyrosine phosphorylation and subsequent platelet aggregation were originally reported to require translocation of CLEC-2 into lipid rafts upon ligand engagement (84). However, a later study showed that neither CLEC-2 phosphorylation nor subsequent Syk activation depends on lipid raft integrity, leading to the proposal that lipid raft disruption inhibits the actions of secondary mediators necessary for CLEC-2-triggered platelet aggregation rather than directly interfering with CLEC-2 phosphorylation (85).…”
Section: Key Features Of Hemitam Signaling As Defined By the Prototypmentioning
confidence: 99%